African-American Voting Disenfranchisement from 1965 to the 2018 Midterm Elections of Georgia - CHIBANI, Nour El Houda (My University, 2019)
The aim of this study is to demonstrate a complete assessment of AfricanAmerican voter disenfranchisement throughout the history of the United States; ultimately concentrating on the 21st century to evaluate the evolving forms of disenfranchisement. For that purpose, the 2018 Georgia midterm election was selected as a case study in order to collect and investigate evidence of voter suppression. In this dissertation, the techniques of voter disenfranchisement are explained with the purpose of potentially identifying their presence in the Georgia midterms. By researching voter turnout alongside demographic data of voters, findings in the study have shown that suppression techniques have been genuinely used during the aforementioned elections. In fact, discriminatory laws to disenfranchise African-Americans continue to exist in the 21st century; and it is clear that the American electoral system is still biased against AfricanAmericans through the different laws that are designed to prevent such minority groups from voting.
Keywords: Electoral system - U.S. Constitution - African-Americans - Reconstruction Era - Voting Rights Act - disenfranchisement